Supporting teacher candidates' multidimensional reflection: a model and a protocol. Issue 2 (4th March 2021) - Brantley-Dias, Laurie; Puvirajah, Anton; Dias, Michael
ABSTRACT: In this conceptual paper, we present a professional practice-oriented Multidimensional Model of Reflective Practice (MMRP) and a Critical Incident Reflection (CIR) protocol as worthwhile tools for supporting teacher candidates (TCs) to become more self-directed, multi-faceted, and holistic in their reflective practice. The model presents reflection as a complex endeavor situated in a dynamic milieu. It emphasizes the complementary nature of professional competencies of knowledge, skills, and disposition, and the interrogation of an incident through technical, contextual, and critical reflection as well as reflection-in, -on, and -for-action. The CIR protocol provides scaffolding support for TCs as they move toward becoming independent reflective practitioners. Together, the MMRP and CIR protocol facilitate multidimensional reflection. We present a case for providing a more deliberate support for reflection. In doing this, we define reflection, highlight its common frameworks, and discuss the significance of intentional and systematic reflection on professional competencies. In the conclusion, we bring these ideas together to discuss the implications for a self-directed and agentic approach to reflection and professional growth.